The influence of materials dosing order and shear forces on the properties of high density polyethylene/ground tire rubber blends obtained in co-rotating twin screw extruder - Formela, K.; Cysewska, M; Haponiuk, J. (Polimery, 2014)
Thermoplastic compositions of high density polyethylene (PE-HD) containing 50 wt % ground tire rubber (GTR) were obtained using co-rotating twin screw extruder. The effects of dosing order of raw materials and shear forces generated during intense mixing on the extruder operating parameters, mass flow rate, static mechanical properties (tensile strength, elongation at break, hardness and abrasion resistance), dynamic mechanical properties, thermal properties and morphology of the obtained products were investigated. It was found that, under the studied conditions, the order of raw materials addition and the shear forces (estimated from the rotational speed) affected the changes in screw torque, melt temperature at the exit of the extrusion die and mass flow rate of the produced blend, whereas they had no significant effect on the static mechanical properties. Thermal analysis using DMA, DSC and TG methods showed similar thermal properties of the studied thermoplastic compositions. It was assessed that the surface morphology of the obtained blends also depends on the two factors mentioned above, which can result from the partial plasticization of the plastomer matrix by low-molecular products of ground tire rubber reclaiming.